HIBAH ORANG TUA KEPADA ANAK MENURUT PERSFEKTIF HUKUM PERDATA DAN HUKUM ISLAM PADA MASYARAKAT DI KELURAHAN BETUNGAN KOTA BENGKULU - Yuvita, Yuvita (UIN Fatmawati Sukarno Bengkulu, 2018)
This research raises the problem about the implementation of parent grants to children between justice and equity in urban village of Bengkulu. This research method using qualitative research method. The results of this study concluded that the implementation of parental grants to children in the perspective of civil law in the community in Betungan Village Bengkulu City has implemented a grant in accordance with article 1667 contained in the Book of Civil Law, an agreement, with which a grantee deliver a good Free of charge, without being able to withdraw it, for the benefit of a person who received the delivery of the merchandise. The law only recognizes grants among the living. (KUHPerd 170, 172ff., 179, 913, 1314, 1675, 1683, 1688.). Implementation of parent grants to children in the perspective of Islamic law in the community in Betungan Village Bengkulu City, Implementation of grants conducted by the community in Betungan Village has been implemented well, and follow the rules in accordance with the provisions. Being fair and equating giving to children is obligatory. Doing tafdhil (exaggeration) is forbidden, except when there are factors that allow it. It is permissible to treat others against fellow children if there are any exclusionary factors justified in the case of a disability that makes a person unable to work in search of a livelihood such as paralysis, blindness, inability to work, to seek knowledge and others